MicroRNAs as serum biomarkers for periodontitis. (18th April 2016) - Tomofuji, Takaaki; Yoneda, Toshiki; Machida, Tatsuya; Ekuni, Daisuke; Azuma, Tetsuji; Kataoka, Kota; Maruyama, Takayuki; Morita, Manabu
Abstract: Aim: Studies demonstrated that periodontitis modulates microRNA (miRNAs) expression rates in periodontal tissue. However, the relationship between periodontitis and miRNAs profile in circulation remains unclear. In this study, we investigated the effects of periodontitis on serum miRNAs profile in a rat model. Material and Methods: Male Wistar rats ( n  = 32, 8 weeks old) were divided into four groups of eight rats each. The control groups received no treatment for 2 or 4 weeks. In the other two groups, periodontitis was ligature induced for 2 or 4 weeks. Serum miRNAs expression profiles of each group were compared. Results: Ligation around teeth induced periodontal inflammation at 2 weeks and periodontal tissue destruction at 4 weeks. Microarray results showed that 25 miRNAs were expressed with a <0.5 or >2 difference between the control and periodontitis groups at 4 weeks. Results of real‐time PCR revealed that the periodontitis group up‐regulated expression rates of serum miR‐207 and miR‐495 at 2 weeks, and miR‐376b‐3p at 4 weeks ( p  <   0.05). Conclusion: Serum miRNAs (miR‐207, miR‐495, and miR‐376b‐3p) could be valuable biomarkers for periodontitis.